Chapter Lingue letterarie storiche in ambito culturale serbo: alcuni problemi di codifica HTML - Steenwijk, Han (Biblioteca di Studi Slavistici, 2019)
In HTML pages the language of the document content is indicated by so-called language tags. The present paper explores the various meanings the primary language subtag can denote within the context of 18th and early 19th century literary Serbian. Particular attention is paid to the status of slavenosrpski. As has been shown before when using ISO language tags, their meaning is too broad for direct application within linguistic analyses. The primary subtags will therefore have to be extended, along the lines defined in BCP 47, in order to arrive at meaningful language tags.